Integrating Climate Model Data into Power System Planning - Chattopadhyay, Debabrata; Jordan, Rhonda L. (World Bank, Washington, DC, 2015)
Significant multiyear and multi decade variations in intermittent renewable resources hold major implications for power system investments. They have been using extensive hydrology data for many years to represent hydrological risks in their planning. Climate model data are particularly suited for the assessment of longer-term variability. A good grasp of seasonal, multiyear, and multi decade trends is essential in assessing the economic merits of investments in renewable resources and the extent to which such resources can complement one other or may need to be backed up by further investments in nonrenewable sources. For instance, planners of hydro-dominated systems have learned to use risk-based criteria such as so-called 1-in-50-year drought coverage to deal with the risk posed by extremely dry years. That climate models can provide scenarios over several decades makes them equally applicable to wind and solar planning. Good-quality data generated by climate models - both historical and projected over decades are available for all countries at little or no cost. Such data can and should form part of power system planning, complementing more detailed, but expensive, renewable energy resource mapping and actual observations and measurements of wind, solar, and hydro power.